Pengaruh Motivasi, Kreativitas dan Mata Kuliah Startup Terhadap Minat Mahasiswa Membangun Startup (Studi Pada Mahasiswa Prodi Manajemen Angkatan 2018 Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Tri Dewi Nur Hidayah; Jeni Susyanti; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted to determine the effect of motivation, creativity and startup courses on students' interest in building startups partially. This research is a type of explanatory research that explains the causal relationship between the independent variable and the dependent variable through a hypothesis. The population used in this study were active students of the 2018 class of management study program, FEB, Islamic University of Malang, amounting to 518 students. In this study using a sample of 84 respondents, the sampling technique used in this study was a purposive sampling technique. This study uses quantitative methods, data acquisition using primary data with data collection using a questionnaire method through distributing questionnaires with a Likert scale as a measuring tool for respondents' answers. The data analysis method used is multiple linear regression analysis. The results of this study indicate that motivation has a positive and significant effect on student interest in building startups, creativity has a positive and significant effect on student interest in building startups and startup courses have a positive and significant effect on student interest in building startups in management study program students batch 2018 Faculty of Economics and Business Islamic University of Malang. Keyword: Motivation, Creativity, Startup Courses On Student And Interest In Building Startups